Bicolor silicon ball doped with PEI carbon dots and bipyridyl ruthenium, preparation method of bicolor silicon ball and copper ion determination system
By doping bicolor silicon spheres with PEI carbon dots and bipyridine ruthenium, the two-color colorimetric detection principle is used to solve the complex and expensive problem of copper ion detection methods in water bodies in the prior art, and the rapid, sensitive and selective copper ion detection effect is achieved.
Patent Information
- Application Number
- CN202411616023.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-25
AI Technical Summary
The existing copper ion detection methods in water bodies rely on expensive instruments and cumbersome sample preparation process, and are not suitable for widespread applications in daily life.
Using bicolor silicon spheres doped with PEI carbon dots and bipyridine ruthenium, the PEI carbon dots and bipyridine ruthenium dots into silica nanoparticles through the preparation method, and the bicolor colorimetric detection of copper ions is achieved using the red fluorescence of Ru(bpy)32+ and the internal filtering effect of PEI-CQDs.
It realizes fast, convenient, selective and high sensitivity detection of copper ions, and can conduct on-site real-time monitoring without relying on large and valuable analytical instruments, which has good application value.
Smart Images

Figure CN119505865A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper ion detection, and in particular to a two-color silicon ball doped with PEI carbon dots and bipyridine ruthenium, a preparation method thereof, and a copper ion determination system. Background Art
[0002] With the development of industrial technology, copper ion pollution in mining, metal smelting and other industries has become an environmental problem that people have to face. Copper exists in various forms in water and is distributed in various components of aquatic ecosystems. Among them, free divalent copper Cu 2+ It is generally recognized by the academic community as the main ion form that produces poisons for aquatic organisms. When the copper ions in aquatic organisms are enriched to a certain amount, symptoms such as physiological obstruction, developmental stagnation and even death will appear, which will lead to structural defects and functional loss of the aquatic ecosystem, and eventually collapse. Copper has a strong inhibitory effect on cell metabolism, which can poison the microbial flora in the water, block the decomposition of organic matter, cause the water body to lose its self-purification function, and ultimately damage the aquatic ecosystem. When there are excessive copper ions in the water, the water ecology will be destroyed, the transparency of the water will be reduced, it will be stained and have an odor. In addition, copper plays an important role in many physiological activities such as bone growth, cell respiration and connective tissue formation. Its concentration is higher or lower than normal levels will have adverse effects on the body. For example, a lack of copper can cause anemia, and the accumulation of excessive copper ions in the human body can cause renal necrosis, nervous system diseases and even death. According to the standards published by the World Health Organization (WHO), direct drinking water containing Cu 2+ is 1.25 mmol / l. 2+ The maximum content of copper is 2.0 mg / L (32 μmol / L), and the Chinese standard also stipulates that the limit of copper in drinking water is 1.0 mg / L (16 μmol / L). Therefore, the design and application of copper ion probe is an important research topic.
[0003] At present, the commonly used methods for copper ion detection in water are: spectrophotometry, electrochemical method, electrochemiluminescence, atomic absorption spectroscopy, inductively coupled plasma mass spectrometry, etc. These methods rely on expensive instruments and require cumbersome sample preparation and skilled operation techniques, which are not conducive to widespread application in daily life. Therefore, it is necessary to study the Cu ion detector with fast response time, high sensitivity, good selectivity and simple operation. 2+ Sensors are of great significance. Summary of the invention
[0004] The object of the present invention is to provide a two-color silicon ball doped with PEI carbon dots and bipyridine ruthenium, which has obvious response to copper ions and good selectivity.
[0005] Another object of the present invention is to provide a method for preparing two-color silicon spheres doped with PEI carbon dots and bipyridine ruthenium, which is simple to operate and has controllable parameters.
[0006] The third object of the present invention is to provide a PEIQDs-Ru-SiO2 two-color visual copper ion determination system, which is fast, convenient, selective and highly sensitive.
[0007] The present invention solves the technical problem by adopting the following technical solutions.
[0008] The present invention provides a method for preparing a two-color silicon sphere doped with PEI carbon dots and bipyridine ruthenium, comprising the following steps:
[0009] S1, stirring and dissolving citric acid, polyethyleneimine and double distilled water, and then pre-reacting to obtain a gel-like substance;
[0010] S2, the gel-like substance is kept heated and double distilled water is added in portions to react, and after dilution, a hydrophilic carbon quantum dot solution wrapped with PEI is obtained;
[0011] S3, mixing tetraethyl orthosilicate, ammonia water, water and ethanol and reacting them to obtain a first reaction solution;
[0012] S4, adding the bipyridine ruthenium solution to the first reaction solution for reaction to obtain a second reaction solution;
[0013] S5. After adding the PEI-wrapped hydrophilic carbon quantum dot solution to the second reaction solution for reaction, washing and drying are performed to obtain two-color silicon spheres doped with PEI carbon dots and bipyridine ruthenium (PEIQDs-Ru-SiO2).
[0014] The invention provides a two-color silicon ball doped with PEI carbon dots and bipyridine ruthenium, which is prepared according to the preparation method.
[0015] The present invention proposes a PEIQDs-Ru-SiO2 two-color visualized copper ion determination system, comprising a phosphate buffer solution (PBS buffer) and a two-color silicon sphere solution doped with PEI carbon dots and ruthenium bipyridine, wherein the two-color silicon sphere solution doped with PEI carbon dots and ruthenium bipyridine is an aqueous solution of the two-color silicon spheres doped with PEI carbon dots and ruthenium bipyridine.
[0016] The beneficial effects of the two-color silicon spheres doped with PEI carbon dots and bipyridine ruthenium and the preparation method thereof, and the copper ion determination system of the embodiments of the present invention are:
[0017] The present invention prepares bicolor silicon spheres doped with PEI carbon dots and bipyridine ruthenium by the Stober method. Carbon quantum dots have excellent optical properties and stability. Silicon spheres can be used as dispersants for pigments, thereby helping the pigments to be evenly dispersed in liquids, thereby improving the stability and color vividness of the pigments. The present invention combines PEI-CQDs and bipyridine ruthenium Ru(bpy)3 2+Doping into silica nanoparticles using Ru(bpy)3 2+ The red fluorescence is used as the background color, combined with Cu 2+ The fluorescence signal of PEIQDs-Ru-SiO2 has a significant response to copper ions and good selectivity, so it can be used for Cu 2+ The visual detection has the advantages of being fast, convenient, cheap, simple, selective, and highly sensitive, and is very meaningful for on-site real-time monitoring of copper ion concentration. The PEIQDs-Ru-SiO2 two-color visual copper ion determination system of the present invention has the advantages of not relying on large and expensive analytical instruments, being able to be observed with the naked eye, and having a fast response time, and can realize on-site rapid visual detection of copper ions, and has good application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 Comparison of fluorescence photos of PEIQDs-Ru-SiO2 before and after centrifugation;
[0020] Figure 2 HRTEM image of PEIQDs-Ru-SiO2 of Example 1 of the present invention;
[0021] Figure 3 XRD diagram of PEIQDs-Ru-SiO2 and blank silicon spheres in Example 1 of the present invention;
[0022] Figure 4 It is a N2 adsorption-desorption curve diagram of PEIQDs-Ru-SiO2 and blank silicon spheres in Example 1 of the present invention;
[0023] Figure 5 The infrared spectra of blank silicon spheres, PEIQDs-Ru-SiO2, PEI carbon dots and bipyridine ruthenium;
[0024] Figure 6 The fluorescence spectra of PEIQDs-Ru-SiO2 solution before and after adding copper ions and the fluorescence response photos under 365nm ultraviolet light;
[0025] Figure 7This is the effect of pH value on fluorescence intensity of PEIQDs-Ru-SiO2 solution without copper ions and with copper ions;
[0026] Figure 8 This is a graph showing the change of fluorescence quenching of PEIQDs-Ru-SiO2 solution over time;
[0027] Fig. 9 is the relationship between the concentration and fluorescence intensity of the PEIQDs-Ru-SiO2 composite material;
[0028] Fig.10 The fluorescence response diagram of different metal ions to the PEIQDs-Ru-SiO2 dual-color determination of copper ion system;
[0029] Fig.11 It is a linear relationship diagram between copper ion concentration and fluorescence intensity of PEIQDs-Ru-SiO2 at 445nm and 610nm;
[0030] Fig.12 Adding different concentrations of Cu to PEIQDs-Ru-SiO2 2+ Then the fluorescence photos and corresponding fluorescence curves under UV light at 365nm;
[0031] Fig.13 Adding different concentrations of Cu to PEIQDs 2+ Then the fluorescence photograph and corresponding fluorescence curve graph were taken under UV light at 365nm.
[0032] Fig.14 Adding different concentrations of Cu to PEIQDs-SiO2 2+ Then the fluorescence photograph and corresponding fluorescence curve graph were taken under UV light at 365nm. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0034] The following specifically describes the two-color silicon spheres doped with PEI carbon dots and bipyridine ruthenium, the preparation method thereof, and the copper ion determination system according to the embodiments of the present invention.
[0035] The present invention provides a method for preparing a bicolor silicon sphere doped with PEI carbon dots and bipyridine ruthenium, comprising the following steps:
[0036] S1. Stir and dissolve citric acid, polyethyleneimine and double distilled water, and then perform a pre-reaction to obtain a gel-like substance.
[0037] Furthermore, in a preferred embodiment of the present invention, the mass volume ratio of the citric acid, the polyethyleneimine and the first secondary distilled water is 1:0.4-0.6:8-12 (g / g / mL).
[0038] Furthermore, in a preferred embodiment of the present invention, the pre-reaction temperature is 75-85°C, and the pre-reaction time is 16-20 hours. Preferably, the pre-reaction temperature is 80°C, and the pre-reaction time is 18 hours.
[0039] S2, the gel-like substance is kept heated and double distilled water is added in batches for reaction, and after dilution, a hydrophilic carbon quantum dot solution wrapped in PEI is obtained. Carbon quantum dots are an emerging carbon nanomaterial that has special photoelectric properties like traditional compound semiconductor quantum dots, and has advantages that traditional quantum dots do not have, such as low toxicity, good biocompatibility, good stability, and easy labeling.
[0040] Furthermore, in a preferred embodiment of the present invention, the step of keeping the gel-like substance heated and adding double distilled water in portions to react is: placing the gel-like substance in a flat heater and keeping it heated at 190-210°C, then adding the double distilled water to boiling, and when the water evaporates to a viscous liquid that is quickly burnt, adding the double distilled water again, repeating the above steps 2-4 times, and then diluting to obtain the PEI-wrapped hydrophilic carbon quantum dot solution.
[0041] S3, mixing tetraethyl orthosilicate, ammonia water, water and ethanol and reacting them to obtain a first reaction solution.
[0042] Furthermore, in a preferred embodiment of the present invention, the volume ratio of the tetraethyl orthosilicate, the ammonia water, the water and the ethanol is 1.5-1.7:1.3-1.5:1:17-18, and the reaction time is 50-70 min.
[0043] S4. Add the ruthenium bipyridine solution to the first reaction solution for reaction to obtain a second reaction solution.
[0044] Furthermore, in a preferred embodiment of the present invention, the volume ratio of the tetraethyl orthosilicate to the ruthenium bipyridine solution is 1.5-1.7:1, the molar concentration of the ruthenium bipyridine solution is 0.008-0.012 mol / L, and the reaction time is 2.5-3.5 h.
[0045] S5. After adding the PEI-wrapped hydrophilic carbon quantum dot solution to the second reaction solution for reaction, washing and vacuum drying are performed to obtain bicolor silicon spheres doped with PEI carbon dots and bipyridine ruthenium. Preferably, ethanol is used for washing. Nano-silicon dioxide wrapped with fluorescent substances has the advantages of strong photosensitivity, high photostability, good surface chemical activity and bioaffinity, easy surface modification, simple and easy synthesis conditions, and the like, and can therefore be used in biosensors and immunoassays at the molecular level.
[0046] Furthermore, in a preferred embodiment of the present invention, the volume ratio of the tetraethyl orthosilicate to the PEI-encapsulated hydrophilic carbon quantum dot solution is 1.5-1.7:1, the reaction time is 11-13 hours, and the vacuum drying temperature is 55-65°C.
[0047] Carbon quantum dots have excellent optical properties and stability. Silicon spheres can be used as dispersants for pigments, which can help pigments disperse evenly in liquids and improve the stability and color vividness of pigments. Therefore, the present invention combines PEI-CQDs and bipyridine ruthenium Ru(bpy)3 2+ Doping into silica nanoparticles using Ru(bpy)3 2+ The red fluorescence of Cu or the green fluorescence of lustrous essence is used as the background color. 2+ The internal filtering effect of PEI-CQDs can realize the dual-color colorimetric detection of copper ions. Because the mixed color change is more obvious than the single color change, it is easier to observe with the naked eye. The color difference caused by the doping of two different fluorescent substances can also improve the visual detection of Cu ions. 2+ This method has the advantages of not relying on large and expensive analytical instruments, being able to be observed with the naked eye, and having a fast response time, and can achieve on-site rapid visual detection of copper ions.
[0048] The present invention also provides a two-color silicon sphere doped with PEI carbon dots and bipyridine ruthenium, which is prepared according to the preparation method.
[0049] The present invention also provides a PEIQDs-Ru-SiO2 two-color visualized copper ion determination system, comprising a phosphate buffer solution and a two-color silicon sphere solution doped with PEI carbon dots and ruthenium bipyridine, wherein the two-color silicon sphere solution doped with PEI carbon dots and ruthenium bipyridine is an aqueous solution of the two-color silicon spheres doped with PEI carbon dots and ruthenium bipyridine.
[0050] The reaction mechanism of the PEIQDs-Ru-SiO2 dual-color visual copper ion determination system of the present invention is: copper ions react with amino groups on the surface of the PEI carbon dot material to form a complex that is inactive in fluorescence but active in ultraviolet light, and finally suppresses the fluorescence of the carbon quantum dots through the internal filtering effect. However, copper ions have no inhibitory effect on the fluorescence of ruthenium bipyridine, so after adding copper ions, the blue fluorescence of the material will be quenched, highlighting the red fluorescence of ruthenium bipyridine, thereby achieving a good effect of dual-color determination of copper ions.
[0051] Furthermore, in a preferred embodiment of the present invention, the pH of the phosphate buffer solution is 4-6, and the concentration of the two-color silicon sphere solution doped with PEI carbon dots and bipyridine ruthenium is 0.05-0.4 mg / mL.
[0052] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0053] Example 1
[0054] This embodiment provides a two-color silicon sphere doped with PEI carbon dots and bipyridine ruthenium, which is prepared according to the following steps:
[0055] (1) Preparation of PEICQDs: 1 g of citric acid and 0.5 g of polyethyleneimine PEI (M=1800) were weighed in a 25 mL beaker, 10 mL of double distilled water was added, stirred to dissolve, and placed in an oven at 80°C for pre-reaction for 18 hours to obtain a gel-like substance. The gel-like substance was placed in a flat heater and heated at 200°C, and then double distilled water was added to boil. When the water evaporated to a viscous liquid that was almost burnt, a small amount of double distilled water was added, and the process was repeated several times until the color of the solution turned orange-yellow, and diluted to 10 mL to obtain a PEI-encapsulated hydrophilic carbon quantum dot solution.
[0056] (2) Preparation of two-color silicon spheres doped with PEI carbon dots and ruthenium bipyridine: 0.8 mL of tetraethyl orthosilicate (TEOS), 0.7 mL of ammonia water, 0.5 mL of water and 8.8 mL of ethanol were added to a round-bottom flask, stirred evenly at room temperature for 1 hour to allow for full reaction, and then 500 uL of 0.01 M ruthenium bipyridine solution was added to react for 3 hours. Then 500 uL of PEI-encapsulated hydrophilic carbon quantum dot solution was added to react for 12 hours, washed with ethanol several times and vacuum dried at 60°C to obtain two-color silicon spheres doped with PEI carbon dots and ruthenium bipyridine (PEIQDs-Ru-SiO2).
[0057] Example 2
[0058] This embodiment provides a two-color silicon sphere doped with PEI carbon dots and bipyridine ruthenium, which is prepared according to the following steps:
[0059] (1) Preparation of PEICQDs: 1 g of citric acid and 0.5 g of polyethyleneimine PEI (M=1800) were weighed in a 25 mL beaker, 10 mL of double distilled water was added, stirred to dissolve, and placed in an oven at 85°C for pre-reaction for 16 hours to obtain a gel-like substance. The gel-like substance was placed in a flat heater and heated at 200°C, and then double distilled water was added to boil. When the water evaporated to a viscous liquid that was almost burnt, a small amount of double distilled water was added, and the process was repeated several times until the color of the solution changed to orange-yellow, and diluted to 10 mL to obtain a PEI-encapsulated hydrophilic carbon quantum dot solution.
[0060] (2) Preparation of two-color silicon spheres doped with PEI carbon dots and ruthenium bipyridine: 0.8 mL of tetraethyl orthosilicate (TEOS), 0.7 mL of ammonia water, 0.5 mL of water and 8.8 mL of ethanol were added to a round-bottom flask, stirred evenly at room temperature for 1 hour to allow for full reaction, and then 500 uL of 0.01 M ruthenium bipyridine solution was added to react for 3 hours. Then 500 uL of PEI-encapsulated hydrophilic carbon quantum dot solution was added to react for 12 hours, washed with ethanol several times and vacuum dried at 60°C to obtain two-color silicon spheres doped with PEI carbon dots and ruthenium bipyridine (PEIQDs-Ru-SiO2).
[0061] Test Example 1
[0062] In this test example, two-color silicon spheres doped with PEI carbon dots and ruthenium bipyridine (PEIQDs-Ru-SiO2) were observed before and after centrifugation under 365nm ultraviolet light.
[0063] like Figure 1 The figure shows the fluorescence photo comparison of PEIQDs-Ru-SiO2 before and after centrifugation. Figure 1 (A) is the fluorescence photo of PEIQDs-Ru-SiO2 before centrifugation; Figure 1 (B) is a fluorescence photo of PEIQDs-Ru-SiO2 before centrifugation. Figure 1 It can be seen that under 365nm ultraviolet light, the PEIQDs-Ru-SiO2 synthesized in Example 1 emits uniform bright orange fluorescence, which is a mixture of blue light emitted by PEI carbon dots and red light emitted by bipyridine ruthenium. After centrifugation of the material, it can be found that the supernatant is colorless, indicating that both PEI carbon dots and bipyridine ruthenium can be well encapsulated in the silicon sphere.
[0064] Test Example 2
[0065] This experimental example uses a high-resolution field emission lens (HRTEM) to analyze the shape, size and dispersion of PEIQDs-Ru-SiO2 in Example 1.
[0066] like Figure 2The HRTEM image of PEIQDs-Ru-SiO2 of Example 1 is shown. Figure 2 It can be seen that the nanomaterial has uniform size, the particles are regular spherical and the diameter is about 300nm.
[0067] Test Example 3
[0068] In this test example, X-ray diffractometer technology (XRD) was used to characterize the PEIQDs-Ru-SiO2 and blank silicon spheres of Example 1. At the same time, N2 adsorption and desorption experiments were used to investigate the specific surface area of PEIQDs-Ru-SiO2.
[0069] like Figure 3 The XRD patterns of PEIQDs-Ru-SiO2 and blank silicon spheres in Example 1 are shown. Figure 3 It can be seen that the doping of carbon dots and ruthenium bipyridine did not change the crystalline structure of silica nanoparticles.
[0070] like Figure 4 The graph shows the N2 adsorption-desorption curves of PEIQDs-Ru-SiO2 and blank silicon spheres in Example 1. According to the software of the physical adsorption instrument, the specific surface area of the blank silicon sphere can be measured to be 7.2496 cm 3 / g, pore size 10.777nm; the specific surface area of the two-color silicon sphere doped with PEI carbon dots and bipyridine ruthenium is 8.1617cm 3 / g, pore size 8.324nm. This shows that PEIQDs-Ru-SiO2 is a mesoporous material, and the doping of carbon dots and bipyridine ruthenium has little effect on the specific surface area of silicon spheres, but can lead to a slight decrease in their pore size.
[0071] Test Example 4
[0072] In this test example, the PEIQDs-Ru-SiO2 and blank silicon spheres of Example 1 were characterized by infrared. The samples were prepared by KBr tableting method, and the wave number range was 4000~400cm -1 The infrared spectra of blank silicon spheres, PEIQDs-Ru-SiO2, PEI carbon dots and bipyridine ruthenium were measured respectively.
[0073] like Figure 5 Shown are the infrared spectra of blank silicon spheres, PEIQDs-Ru-SiO2, PEI carbon dots and bipyridine ruthenium. Figure 5 In the figure, curve a is the infrared spectrum of blank silicon spheres; curve b is the infrared spectrum of two-color silicon spheres doped with PEI carbon dots and bipyridine ruthenium; curve c is the infrared spectrum of bipyridine ruthenium; curve d is the infrared spectrum of PEI carbon dots. By comparing curve a and curve b, it can be found that PEIQDs-Ru-SiO2 is higher than blank silicon spheres at 2950 and 2820 cm -1There is an additional vibration absorption peak of -CH2 at 1700cm -1 There is an additional stretching vibration absorption peak of -CONH-, both of which are from PEI carbon dots (curve d). Since ruthenium bipyridine (curve c) is wrapped in silicon spheres, the characteristic absorption peaks on doped silicon spheres can still be found, but not very obvious. Infrared characterization also shows that both PEI carbon dots and ruthenium bipyridine can be doped into silicon spheres.
[0074] Test Example 5
[0075] This experimental example studies the fluorescence spectrum of the PEIQDs-Ru-SiO2 solution before and after adding copper ions to 0.1M PBS (pH=4.0) and the fluorescence response under 365nm ultraviolet light.
[0076] like Figure 6 Shown are the fluorescence spectra of PEIQDs-Ru-SiO2 solution before and after adding copper ions and the fluorescence response photos under 365nm ultraviolet light. Figure 6 In the figure, curve 1 is the fluorescence spectrum of the PEIQDs-Ru-SiO2 solution before adding copper ions; curve 2 is the fluorescence spectrum of the PEIQDs-Ru-SiO2 solution after adding copper ions. The left side is the fluorescence response photo before adding copper ions, and the right side is the fluorescence response photo after adding copper ions. Figure 6 It can be seen that in the absence of copper ions, the material emits mixed color fluorescence ranging from blue to red under 365nm ultraviolet light, and there are two emission peaks in its fluorescence spectrum at 445nm and 610nm, of which 445nm is the emission peak of PEI carbon dots and 610nm is the emission peak of bipyridine ruthenium. When copper ions are added, the emission peak at 445nm is basically completely quenched, but the emission peak at 610nm is basically unaffected, so that the material shows the color of bipyridine ruthenium, that is, red fluorescence. This phenomenon can be used to construct a dual-color visual copper ion determination system using PEIQDs-Ru-SiO2.
[0077] Test Example 6
[0078] After confirming that PEIQDs-Ru-SiO2 can be used for dual-color determination of copper ions, the optimal experimental conditions for detecting copper ions can be determined by examining the effects of various experimental conditions (such as pH, time, and PEIQDs-Ru-SiO2 concentration) on the reaction system. At the same time, the reaction mechanism of the PEIQDs-Ru-SiO2 dual-color copper ion determination system can be preliminarily discussed. In this test example, 0.1 mg mL -1The influence of pH value = 3.0-12.0 on the PEIQDs-Ru-SiO2 dual-color determination of copper ions was studied when PEIQDs-Ru-SiO2 did not contain or contained 10 μM copper ions. The specific steps were as follows: 10 μL of 10 mg mL -1 PEIQDs-Ru-SiO2, 980 μL of PBS buffer with pH = (2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0), and 10 μL of 10 -3 mol / L copper ion solution, and measure the fluorescence spectrum of the solution before and after adding copper ions.
[0079] like Figure 7 The figure shows the effect of pH value on fluorescence intensity of PEIQDs-Ru-SiO2 solution without copper ions and with copper ions. Figure 7 It can be seen that the effect of copper ions on fluorescence quenching can achieve satisfactory results under the conditions of pH = 4, 5 and 6. This is consistent with the results of copper ion determination using PEI carbon dots, but under the condition of pH = 4, the interference of other ions on the system will be relatively small, so pH = 4.0 is determined to be the optimal pH of the system.
[0080] Test Example 7
[0081] This test case studies the effect of time on the PEIQDs-Ru-SiO2 dual-color determination of copper ions. The specific steps are: add 10μL 10mg mL -1 PEIQDs-Ru-SiO2, 980 μL of PBS buffer solution with pH = 4.0, and measure its fluorescence spectrum. Then, 10 μL of 10 -3 mol / L copper ion solution, and the fluorescence spectrum was measured once at 1, 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, and 60 min respectively.
[0082] like Figure 8 The graph shows the change of fluorescence quenching of PEIQDs-Ru-SiO2 solution over time. Figure 8 It can be seen that in the PBS buffer solution at pH = 4, 0.1 mg mL -1 PEIQDs-Ru-SiO2 solution without adding 10 μmol L -1 The fluorescence intensity ratio of copper ions is 445 / I 610 , after adding 10 μmol L -1The copper ions quenched nearly 75% within one minute, and the fluorescence intensity remained unchanged within the next hour. This result shows that the fluorescence quenching of PEIQDs-Ru-SiO2 by copper ions is completed in a very short time, and the fluorescence intensity remains basically unchanged for a long time afterwards, proving that PEIQDs-Ru-SiO2 has a short response time and good signal stability as a copper ion sensor.
[0083] Test Example 8
[0084] This test case studies the effect of PEIQDs-Ru-SiO2 concentration on the PEIQDs-Ru-SiO2 dual-color determination of copper ions. Since the PEIQDs-Ru-SiO2 dual-color determination of copper ions is based on the fluorescence quenching of PEIQDs-Ru-SiO2 materials, the concentration of PEIQDs-Ru-SiO2 must fall within the linear response range. The specific steps are: add 10 μL (5, 10, 20, 25, 30, 40, 50, 75, 100 mg mL -1 )PEIQDs-Ru-SiO2, 990 μL of PBS buffer solution with pH = 4.0, and measure its fluorescence spectrum after reacting for 1 min.
[0085] like Fig. 9 The graph shows the relationship between the concentration and fluorescence intensity of the PEIQDs-Ru-SiO2 composite material. Fig. 9 It can be seen that in the range of 0.05 to 0.4 mg mL -1 Within the concentration range, the concentration of PEIQDs-Ru-SiO2 composite material and its fluorescence intensity showed a good linear relationship, but the concentration was higher than 0.4 mg mL -1 When the fluorescence response deviates from the linearity, the fluorescence response deviates from the linearity. Generally speaking, under the condition of the same concentration of inhibitor, the low concentration of fluorescent probe helps to improve the sensitivity of inhibition. However, too low concentration of fluorescent probe will lead to an increase in the noise ratio. In order to obtain the maximum signal-to-noise ratio and the lowest detection limit, the concentration of PEIQDs-Ru-SiO2 selected by the present invention is 0.1 mg mL -1 .
[0086] In summary, the optimal experimental conditions for the PEIQDs-Ru-SiO2 dual-color determination of copper ions system can be obtained through Experimental Examples 5 to 8 as shown in Table 1:
[0087] Table 1 Optimal experimental conditions for PEIQDs-Ru-SiO2 dual-color determination of copper ions
[0088]
[0089] Test Example 9
[0090] This test example investigated the effect of interfering substances on the detection of copper ions in the PEIQDs-Ru-SiO2 dual-color copper ion determination system under the optimal experimental conditions of the PEIQDs-Ru-SiO2 dual-color copper ion determination system to study the selectivity of the system. The experiment was conducted by taking various common metal ions of the same concentration. Among them, the ion concentration used was 10μM. The specific steps are: add 10μL 10mg mL -1 PEIQDs-Ru-SiO2, 980 μL of PBS buffer with pH = 4.0, and then 10 μL of 10 -3 mol / L metal ion solution (Cu 2+ , Fe 2+ , Hg 2+ 、Ag 2+ , CO 2+ 、Cd 2+ Sn 4+ Sn 2+ 、Zn 2+ 、Ni 2+ , Ca 2+ Mg 2+ , Mn 2+ , Li + Cr 3+ , Pb 2+ 、Na + , K + ) and measure the fluorescence spectrum of the solution before and after adding metal ions.
[0091] like Fig.10 The fluorescence response diagram of different metal ions to the PEIQDs-Ru-SiO2 dual-color determination of copper ions is shown. Fig.10 It can be seen that except for slight interference from mercury ions and iron ions, other ions have no response to the fluorescence of PEIQDs-Ru-SiO2, and the detection system has good selectivity.
[0092] Test Example 10
[0093] In this test example, under the optimal experimental conditions for the PEIQDs-Ru-SiO2 dual-color determination of copper ions, different concentrations of copper ions were added to the PEIQDs-Ru-SiO2 solution to study the relationship between the copper ion concentration and the fluorescence intensity of PEIQDs-Ru-SiO2 at 445nm and 610nm. The specific steps are as follows: add 10μL 10mg mL - 1PEIQDs-Ru-SiO2, 980 μL of PBS buffer with pH = 4.0, and then 10 μL (5, 7.5, 10, 25, 50, 75, 100, 250, 500, 750, 1000) μM copper ion solution were added respectively, and their fluorescence spectra were measured.
[0094] like Fig.11 The figure shows the linear relationship between the copper ion concentration and the fluorescence intensity of PEIQDs-Ru-SiO2 at 445nm and 610nm. Fig.11 It can be seen that at 5.0×10 -8 ~1.0×10 -5 In the range of mol / L, the ratio of the copper ion concentration to the fluorescence intensity of PEIQDs-Ru-SiO2 at 445nm and 610nm is I 445 / I 610 There is a good linear relationship, the linear equation is y = -0.35175x + 6.3257, and the linear correlation coefficient is R = 0.9931. The detection limit of this system is 1.0×10 -8 mol / L(S / N=3).
[0095] Test Example 11
[0096] In order to make full use of the dual-color advantage of this material, this experimental example further uses this material to perform visual detection of copper ions. The specific steps are as follows: add 10 μL of 10 mg mL-1 PEIQDs-Ru-SiO2 and 980 μL of pH = 4.0 PBS buffer into a 1.5 mL centrifuge tube, and then add 10 μL of (0, 100, 500, 1000, 10000) μM copper ion solution respectively, pour into a cuvette, take pictures and measure its fluorescence spectrum. At the same time, the response of PEI carbon dots and silicon spheres wrapped with PEI carbon dots to copper ions was further compared. The specific steps were as follows: 10 μL of PEIQDs with the same fluorescence intensity (another group added PEIQDs-SiO2, and the others remained unchanged) and 980 μL of PBS buffer with pH = 4.0 were added into a 1.5 mL centrifuge tube, and then 10 μL (0, 100, 500, 1000, 10000) μM copper ion solution were added respectively, poured into a cuvette, photographed and measured its fluorescence spectrum.
[0097] like Fig.12 The figure shows the addition of different concentrations of Cu to PEIQDs-Ru-SiO2. 2+ Then the fluorescence photo and corresponding fluorescence curve graph under 365nm UV light. Fig.12 (A) is a fluorescent photograph. Fig.12 (B) is a fluorescence curve. Fig.12It can be seen that after adding different concentrations of copper ions, the fluorescence of PEIQDs-Ru-SiO2 shows a regular gradient change, and it can be seen that after adding 10 -6 M C 2+ Compared with the case without Cu 2+ There are obvious changes in the fluorescence photos when the -6 MCu 2+ According to the latest standards published by the World Health Organization (WHO) in 2011, Cu in direct drinking water 2+ The maximum content is 2 mg / L (32 μmol / L), which is within the visual detection range of the PEIQDs-Ru-SiO2 two-color determination of copper ions system of the present invention. Therefore, the visual determination of copper ions using PEIQDs-Ru-SiO2 has good application value.
[0098] like Fig.13 The figure shows the addition of different concentrations of Cu into PEIQDs. 2+ Then the fluorescence photo and corresponding fluorescence curve graph under 365nm UV light. Fig.13 (A) is a fluorescent photograph. Fig.13 (B) is the fluorescence curve graph. Fig.14 The figure shows the addition of different concentrations of Cu to PEIQDs-SiO2. 2+ Then the fluorescence photo and corresponding fluorescence curve graph under 365nm UV light. Fig.14 (A) is a fluorescent photograph. Fig.14 (B) is a fluorescence curve. Fig.13 and Fig.14 It can be seen that under the condition of similar fluorescence intensity at 445nm, the visual response of PEI carbon dots and PEI carbon dot-wrapped silicon spheres to copper ions did not achieve obvious gradient differences. It can be concluded that PEIQDs-Ru-SiO2 dual-color visual detection of copper ions has significant advantages over PEI carbon dots and PEI carbon dot-wrapped silicon spheres in the determination of copper ions.
[0099] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing bicolor silicon spheres doped with PEI carbon dots and bipyridine ruthenium, characterized in that: The following steps are involved: S1, stirring and dissolving citric acid, polyethyleneimine and double distilled water, and then pre-reacting to obtain a gel-like substance; S2, the gel-like substance is kept heated and double distilled water is added in portions to react, and after dilution, a hydrophilic carbon quantum dot solution wrapped with PEI is obtained; S3, mixing tetraethyl orthosilicate, ammonia water, water and ethanol and reacting them to obtain a first reaction solution; S4, adding the bipyridine ruthenium solution to the first reaction solution for reaction to obtain a second reaction solution; S5. After adding the PEI-wrapped hydrophilic carbon quantum dot solution into the second reaction solution for reaction, washing and vacuum drying are performed to obtain two-color silicon spheres doped with PEI carbon dots and bipyridine ruthenium.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass volume ratio of the citric acid, the polyethyleneimine and the double distilled water is 1:0.4-0.6:8-12 (g / g / mL).
3. The preparation method according to claim 1, characterized in that: In step S1, the pre-reaction temperature is 75-85° C., and the pre-reaction time is 16-20 hours.
4. The preparation method according to claim 1, characterized in that: In step S2, the gel-like substance is kept heated and double distilled water is added in batches to react as follows: the gel-like substance is placed in a flat heater and kept heated at 190-210° C., then the double distilled water is added to boil, and when the water evaporates to a viscous liquid that is fast coking, the double distilled water is added again, and the above steps are repeated 2-4 times, and then diluted to obtain the PEI-wrapped hydrophilic carbon quantum dot solution.
5. The preparation method according to claim 1, characterized in that: In step S3, the volume ratio of the tetraethyl orthosilicate, the ammonia water, the water and the ethanol is 1.5-1.7:1.3-1.5:1:17-18, and the reaction time is 50-70 min.
6. The preparation method according to claim 1, characterized in that: In step S4, the volume ratio of the tetraethyl orthosilicate to the ruthenium bipyridine solution is 1.5-1.7:1, the molar concentration of the ruthenium bipyridine solution is 0.008-0.012 mol / L, and the reaction time is 2.5-3.5 h.
7. The preparation method according to claim 1, characterized in that: In step S5, the volume ratio of the tetraethyl orthosilicate to the PEI-wrapped hydrophilic carbon quantum dot solution is 1.5-1.7:1, the reaction time is 11-13 hours, and the vacuum drying temperature is 55-65°C.
8. A two-color silicon sphere doped with PEI carbon dots and bipyridine ruthenium, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.
9. A PEIQDs-Ru-SiO2 two-color visual copper ion determination system, characterized in that: It comprises a phosphate buffer solution and a two-color silicon sphere solution doped with PEI carbon dots and bipyridine ruthenium, wherein the two-color silicon sphere solution doped with PEI carbon dots and bipyridine ruthenium is the aqueous solution of the two-color silicon spheres doped with PEI carbon dots and bipyridine ruthenium according to claim 8.
10. The PEIQDs-Ru-SiO2 two-color visual copper ion determination system according to claim 9, characterized in that: The pH of the phosphate buffer solution is 4-6, and the concentration of the two-color silicon sphere solution doped with PEI carbon dots and bipyridine ruthenium is 0.05-0.4 mg / mL.